2021
DOI: 10.3389/fimmu.2021.674739
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GPNMB in Inflammation

Abstract: Inflammation is a response to a lesion in the tissue or infection. This process occurs in a specific manner in the central nervous system and is called neuroinflammation, which is involved in neurodegenerative diseases. GPNMB, an endogenous glycoprotein, has been recently related to inflammation and neuroinflammation. GPNMB is highly expressed in macrophages and microglia, which are cells involved with innate immune response in the periphery and the brain, respectively. Some studies have shown increased levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 84 publications
2
78
0
7
Order By: Relevance
“…GPNMB is an endogenous glycoprotein, and many studies have found that it is related to inflammation and neuroinflammation. GPNMB is highly expressed in macrophages and microglia, which are involved in the innate immune response in the periphery and the brain, respectively [19]. GPNMB has been shown to increase the brain tissue of Parkinson's disease patients and reduce the inflammation of astrocytes [20].…”
Section: Discussionmentioning
confidence: 99%
“…GPNMB is an endogenous glycoprotein, and many studies have found that it is related to inflammation and neuroinflammation. GPNMB is highly expressed in macrophages and microglia, which are involved in the innate immune response in the periphery and the brain, respectively [19]. GPNMB has been shown to increase the brain tissue of Parkinson's disease patients and reduce the inflammation of astrocytes [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in many cell types, such as osteoblasts, melanocytes, hepatocytes and leukocytes. This protein, also named Osteoactivin, has a vast array of biological activities, being involved in processes of cell adhesion and differentiation, tissue remodeling and repair after injury; some studies also reported that GPNMB limits inflammation and inhibits T cell-mediated immune responses (Abdelmagid et al 2008 ; Safadi et al 2001 ; Shikano et al 2001 ; Haralanova-Ilieva et al 2005 ; Ripoll et al 2007 ; Kobayashi et al 2019 ; Chung et al 2020 ; Saade et al 2021 ; Weterman et al 1995 ; Singh et al 2010 ).…”
Section: Main Textmentioning
confidence: 99%
“…We showed that higher plasma levels of the integral part of BBB, the tight junction component (TJP1 42 ), and proteins degrading it (AIMP1 43 and BIN1 44 ), increased the risk of dementias. Moreover, pro-inflammatory C1Q, C1R, CD20, CD11, CDHR5, GPNMB, and IL1β 4549 elevated risk of dementias, whereas anti-inflammatory C4B, IL27, IL37, PTP1B, and SIGGIRR 5054 and barrier protecting IL-17F 55 reduced the risk. In suppression and inhibition, regulatory T-cells suppress, or molecules on B- and T-cells inhibit activation of lymphocytes at peripheral checkpoints.…”
Section: Discussionmentioning
confidence: 99%